Re- Examining Linkages between Financial Development, Openness and Vulnerability of Economic Growth in Rwanda using ARDL Application - Tarchoun, Monaem; Mili, Hela (Migration Letters, 2024)
Investigating the link between the real economy and its factors is vital, as financial development can play a critical role in economic growth and economic vulnerability. This study examines the role of stock financial development and country risk (economic vulnerability) on economic growth, and the moderating influence of country risk in the stock market and economic growth nexus in Rwanda economy over the period of 1995 to 2017. The study employed an econometric technique, including auto-distributive lag (ARDL) for examining long-run and short run relationship, among the variables. The study explored that the economic vulnerbility(EVI) is negatively associated with economic growth.Also, the study highlighted the positive impact of openness and financial development on economic growth. The study also suggests that the financial development is solution to solve the negative impact of economic vulnerability on economic growth. Finally, the study suggests some policy recommendations based on the empirical results.